Investigation of magnetic field effect on MRR, EWR and surface roughness during EDM of AISI420 tool Steel - Efendee, A. M.; Azmir, Azhari; Hasnain, A. R.; Zainal Ariffin, S.; Mukhtar, M. (IOP Publishing, 2021)
Electrical discharge machine (EDM) is a machining process that is not affected by the toughness or hardness of the sample material but the electrical and thermal conductivity. In EDM process, good surface quality can only be produced if low peak current is used but the machining process will take a long time causing material removal rate (MRR) to be too low. While the accumulated machine debris in the machining zone can cause abnormal discharge and disrupt the material removal process. The present research aims to study the magnetic field effect on MRR, EWR and SR for EDM process improvement. In addition to MRR, electrode wear rate (EWR) and surface roughness illustrate the effectiveness of the EDM process. The installation of magnetic devices in the EDM machining area were implemented and the experiments were conducted using graphite electrode and AISI420 as the workpiece. Permanent magnets having 0.54 Tesla were applied to produce magnetic fields during EDM operations. The presence of this magnetic field also contributes to the effectiveness of the flushing process because the evaporated debris will be attracted and attached to the magnet, then purify the spark gap medium for the next discharge process. Dielectric that stays clean and sparks under magnetic field influence increases the effectiveness of the material removal process. Surface roughness from Ra measurement has recorded 12.6% to 28.1% improvement when magnetic devices were applied on EDM. The spark ignition delays and the refinement of EDM spark enhanced the surface quality compared to conventional EDM. Comparison of images through optical microscopy and SEM also proves that the Magnetic Field Assisted EDM (MFAEDM) method is capable of producing better surface quality. This MFAEDM shows that action to hybridize EDM is necessary to increase EDM competency by attaining both of machining efficiency and high quality of surface integrity.